Pengaruh Retail Atmospherics, Shopper Trust, dan Corporate Reputation terhadap Repatronage Intention di Minimarket Jakarta - Jorken Jorken; Keni Keni (Jurnal Bisnis dan Akuntansi, 2022)
Retail industry is an industry with a fairly rapid development. Among the various classes in the retail industry, minimarket retail stores have the highest growth. Hence, the competition in minimarket class is very tight. So, in order to face the competition, then it is necessary to create repatronage intention towards customers. To do so, there are various factors that could create repatronage intention such as retail atmospherics, shopper trust, and corporate reputation. The purpose of this study is to understand the role of retail atmospherics, shopper trust, and corporate reputation as repatronage intention’s predictors at Jakarta minimarket. Descriptive study is used with cross-sectional approach in data collection process. There are 160 valid questionnaires were collected with non-probability sampling method and convenience sampling is used as sampling technique. Furthermore, collected data were analyzed using Partial Least Square-Structural Equation Modelling method. Based on the results, can be concluded that retail atmospherics, shopper trust, and corporate reputation could positively predict towards repatronage intention at Jakarta minimarket.